The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1111/j.1399-3054.2008.01073.x
|View full text |Cite
|
Sign up to set email alerts
|

Potassium influences on yield and quality production for maize, wheat, soybean and cotton

Abstract: Potassium is one of the principle plant nutrients underpinning crop yield production and quality determination. While involved in many physiological processes, potassium's impact on water relations, photosynthesis, assimilate transport and enzyme activation can have direct consequences on crop productivity. Potassium deficiency can lead to a reduction in both the number of leaves produced and the size of individual leaves. Coupling this reduced amount of photosynthetic source material with a reduction in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
379
1
21

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 656 publications
(457 citation statements)
references
References 89 publications
18
379
1
21
Order By: Relevance
“…Potassium fertilization can influence germination and seed vigor since it is an es-sential element for oil synthesis and transport in soybeans [1] [2]. Similar results were obtained by [3], who found that seed vigor was significantly affected by potassium fertilization rates.…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…Potassium fertilization can influence germination and seed vigor since it is an es-sential element for oil synthesis and transport in soybeans [1] [2]. Similar results were obtained by [3], who found that seed vigor was significantly affected by potassium fertilization rates.…”
Section: Introductionsupporting
confidence: 78%
“…There are several reports in the literature showing that the effect of potassium on physiological quality, yield, and chemical composition is due to the natural content of the nutrient in the experimental area. According to [1], it is necessary to carry out experiments in areas of low natural nutrient content.…”
Section: Resultsmentioning
confidence: 99%
“…From the dose that resulted in the MTE of each cultivar, there was a reduction in protein yield (kg ha -1 ), possibly as a direct consequence of the antagonistic effect of K 2 O, which reduced the absorption of other cations, i.e., it had strong competitive effect on the nutrients (Ca, Mg, N and P), negatively influencing the development of the plants (Malavolta, 1980). Pettigrew (2009) andVeiga et al (2010) claim that K plays vital roles and is essential in the synthesis and transport of protein to the organs.…”
Section: Resultsmentioning
confidence: 99%
“…According to Pettigrew (2009) andRengel &Damon (2008), under conditions of low K availability in the soil, soybean cultivars adapted and efficient regarding this nutrient exhibit better production performance.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, K fertilization responses in soybean plants can be achieved by a number of management regimes when the soil tests low for available K (Pettigrew, 2008). Jeffers et al (1982) studying soybean production at three locations, observed high percentages of moldy and dead seeds under conditions of K deficiency, but seed germination was improved by K fertilization.…”
Section: Introductionmentioning
confidence: 99%